Sifat Kimia Cendol Instan Dengan Formulasi Daun Suji Dan Cincau Hijau - Puji Lestari, Bayurini; Dewi, Wike Nurwita (CV. ULIL ALBAB CORP, 2025)
Cendol is one of the most popular traditional foods in Indonesia. The distinctive aroma of pandan leaves (Pandanus amaryllifolius) used in making cendol plays an important role in strengthening the identity of the taste and aroma of traditional culinary. The objective of the research was to determine the chemical characteristics of instant cendol made of green grass jelly (Cycle barbata L.). The rate of increase in water content of instant cendol was measured during storage at room temperature. The research was designed as a factorial randomized block design with two factors as treatments, and each treatment was repeated three times. The first factor was the concentration of green grass jelly (A1 = 0 % , A2 = 10 % , A3 = 20 %), and the second factor was the concentration of Pleomele and Pandanus leaves extract (B1 = 10 % , B2 = 20 %, B3 = 30 %). minutes of rehydration time, 2.07 % of ash content, 2.31% protein content, and 0.121% per week for the rate of increase in water content. The chemical characteristics of A3B2 are a rate of increase in water content of 0.115 per week, ash content of 2.07% and protein content of 2.31%.